Effects of Exogenous Abscisic Acid (ABA) on Carotenoids and Petal Color in Osmanthus fragrans ‘Yanhonggui’ - Yucheng Liu; Bin Dong; Chao Zhang; Liyuan Yang; Yiguang Wang; Hongbo Zhao (Plants, 2020)
Osmanthus fragrans is a well-known native plant in China, and carotenoids are the main group of pigments in the petals. Abscisic acid (ABA) is one of the products of the metabolic pathway of carotenoids. Application of ABA could affect pigmentation of flower petals by changing the carotenoid content. However, little is known about the effects of ABA treatment on carotenoid accumulation in O. fragrans. In this study, different concentrations of ABA (0, 150 and 200 mg/L) were spread on the petals of O. fragrans ‘Yanhonggui’. The petal color of ‘Yanhonggui’ receiving every ABA treatment was deeper than that of the control. The content of total carotenoids in the petals significantly increased with 200 mg/L ABA treatment. In the petals, α-carotene and β-carotene were the predominant carotenoids. The expression of several genes involved in the metabolism of carotenoids increased with 200 mg/L ABA treatment, including PSY1, PDS1, Z-ISO1, ZDS1, CRTISO, NCED3 and CCD4. However, the transcription levels of the latter two carotenoid degradation-related genes were much lower than of the five former carotenoid biosynthesis-related genes; the finding would explain the significant increase in total carotenoids in ‘Yanhonggui’ petals receiving the 200 mg/L ABA treatment.